Pasca Pilihan Raya ke-12 perubahan dan hala tuju politik Malaysia: perspektif Sarawak dan Sabah - Narani, Junaidi @ Saudi (Universiti Teknologi MARA, Sarawak, 2009)
UiTM Sarawak has successfully organized the "Pasca Pilihan Raya ke 12" political forum on 29th August, 2008. It was held in conjunction with the Merdeka month celebration with the theme "Changes and Directions of Malaysian Politics: Sarawak and Sabah Perspectives".